Good long‐term adherence to continuous positive airway pressure therapy in patients with resistant hypertension and sleep apnea. (2nd January 2019) - Campos‐Rodriguez, Francisco; Navarro‐Soriano, Cristina; Reyes‐Nuñez, Nuria; Torres, Gerard; Caballero‐Eraso, Candela; Lloberes, Patricia; Diaz‐Cambriles, Trinidad; Somoza, Maria; Masa, Juan F.; Gonzalez, Monica; Mañas, Eva; de la Peña, Monica; et al.
Abstract: Although adequate adherence is paramount in achieving the beneficial effects of continuous positive airway pressure therapy in patients with obstructive sleep apnea, long‐term adherence and the variables involved in continuous positive airway pressure compliance in patients with resistant hypertension and obstructive sleep apnea are yet unknown. We conducted a prospective, multicentre, observational study in 177 patients recruited from hypertensive units with resistant hypertension confirmed by means of 24‐hr blood pressure monitoring (blood pressure ≥ 130 and/or ≥ 80 mmHg, despite taking at least three antihypertensive drugs or < 130/80 mmHg with > 3 drugs) and obstructive sleep apnea (apnea–hypopnea index ≥ 5 in a respiratory polygraph) who were prescribed continuous positive airway pressure treatment. Good adherence was defined as an average cumulative continuous positive airway pressure use of ≥ 4 hr per night at the end of the follow‐up. A multivariate Cox regression analysis was performed to identify independent predictors of continuous positive airway pressure adherence. Patients were followed for a median of 57.6 (42–72) months after initiating continuous positive airway pressure therapy. At the end of the follow‐up, the median continuous positive airway pressure use was 5.7 (inter‐quartile range 3.9–6.6) hr per night, and 132 patients (74.5%) showed good continuous positive airway pressure adherence. The only baseline variable associated with poor adherence was the presence of previous stroke (hazard ratio 4.00, 95% confidence interval 1.92–8.31). Adequate adherence at 1 month also predicted good adherence at the end of the follow‐up (hazard ratio 14.4, 95% confidence interval 4.94–56). Both variables also predicted adherence at a threshold of 6 hr per night. Our results show that good continuous positive airway pressure adherence is an achievable and feasible goal in patients with resistant hypertension and obstructive sleep apnea. Previous stroke and short‐term adherence predicted long‐term adherence.